2019
DOI: 10.5546/aap.2019.eng.216
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological impact of respiratory syncytial virus and identification of risk factors for severe disease in children hospitalized due to acute respiratory tract infection

Abstract: Introduction: Severe acute respiratory tract infection (ARTI) is a very common cause of hospitalization in pediatrics; respiratory syncytial virus (RSV) is the major etiologic agent. Accurately defining the burden of RSV life-threatening disease (LTD) and its risk factors is a challenge. Objectives: To know the impact of RSV in children hospitalized due to ARTI and describe the risk factors for LTD. Materials and methods: Prospective study in children < 2 years old hospitalized due to ARTI during 2012-2013 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“… 41 Family history of atopy was reported in 3 studies based on univariable analysis with ORs 0.61–1.22. 27 , 28 , 46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 Family history of atopy was reported in 3 studies based on univariable analysis with ORs 0.61–1.22. 27 , 28 , 46 …”
Section: Resultsmentioning
confidence: 99%
“… 28 , 46 Additionally, 1 study identified a significant association between over-crowding and poor outcomes in male children with OR 2.36 in multivariable analysis; however, for female children the OR was not significant. 27 Precarious home, defined as no sewage system at home or household use of wood as a cooking fuel, was identified as a significant risk factor in 2 studies based on multivariable analyses with ORs 1.66–1.72. 28 , 39 Vulnerable mother, living far from hospital and indigenous ethnicity were each reported in 1 study, but were not significant risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…La adecuada evaluación clínica inicial, el monitoreo estricto y el conocimiento de otras posibles etiologías infecciosas, pueden facilitar el inicio temprano de una terapia dirigida, en especial en pacientes de alto riesgo como prematuros, con patología atópica moderada a severa, trisomía 21, tabaquismo pasivo o en inmunodeficiencia congénita o adquirida. 37,38 La infección por VSR sigue siendo una de las más comunes en la población general que afecta a niños menores de 5 años, generando alta de morbimortalidad en aquellos con factores de riesgo o en menores de 1 año. Hasta 1% de los pacientes infectados por este agente pueden desarrollar alteraciones neurológicas, ya sea por infección directa del sistema nervioso central o por los cambios secundarios a las adaptaciones neuroendocrinas ante la injuria pulmonar y la hipoxemia, que incluyen apnea central y convulsiones.…”
Section: I S C U S I ó Nunclassified
“…Gastrointestinal symptoms were also identified in other studies (4,11) . Such symptoms should be further investigated, as they are common in other viral infections of the respiratory tract such as respiratory syncytial virus (44) .…”
Section: Clinical Status Recommendationsmentioning
confidence: 99%